Association between the dietary index for gut microbiota and metabolic syndrome: the mediating role of the dietary inflammatory index - Han, Yu-Nan; Wang, Yong-Xiang; Xiong, Cheng-Yue; Li, Lin; Mao, Ru-Meng (Frontiers in Nutrition, 2025)
BackgroundMetabolic syndrome (MetS) poses a huge global public health challenge. The dietary index for gut microbiota (DI-GM) measures the influence of diets on the microbiome, but its link with the odds of MetS is elusive. This paper examined the link between DI-GM and MetS and investigated the mediating role of the dietary inflammatory index (DII).MethodsData were sourced from the 2007–2018 NHANES for adults diagnosed with MetS. A total of 20,999 participants were included in the analysis. Dietary data were recorded via two 24-h dietary recalls, from which DI-GM and DII were calculated. Multivariate weighted logistic regression and restricted cubic spline (RCS) analyses were leveraged to assess the link between DI-GM and MetS. Mediation analysis was implemented to determine the role of DII in this association. Subgroup and sensitivity analyses were also implemented.ResultsAfter adjusting for all covariates, participants in the highest DI-GM scores (Q4) had a greatly lower odds of MetS compared to those in the lowest DI-GM group (Q1) (OR = 0.80, 95% CI = 0.69–0.92, p = 0.003). The RCS analysis noted a linear negative link between DI-GM and MetS (P for nonlinear = 0.414). DII partially mediated the correlation between DI-GM and MetS [Indirect effect estimate = −0.00265, 95% CI: (−0.00445, −0.00167), p < 0.001]. Subgroup analysis showed consistent negative associations between higher DI-GM (Q4) and MetS across various demographic and lifestyle subgroups, with no statistically significant interactions observed (P interaction > 0.05).ConclusionHigh DI-GM levels are linked with a significantly reduced odds of MetS, with DII partially mediating this association.